2007
DOI: 10.1016/j.mad.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Copper supplementation increases yeast life span under conditions requiring respiratory metabolism

Abstract: To further exploit yeast as a model for cellular aging we have modified the replicative life span assay to force respiration, by replacing glucose with the non-fermentable carbon source glycerol. The growth rates of several different strains varied greatly, with doubling times ranging from 2.7 to 7 hours. Life spans of all strains were lower on media containing glycerol than on media containing glucose. However, supplementation of glycerol-containing media with copper resulted in increases in life span of betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Yeast, being facultative anaerobes, generate energy primarily from fermentation when glucose is available and switch to a primarily respiratory growth state either when glucose is depleted or when they are grown on a non-fermentable carbon source such as glycerol (Gancedo & Serrano 1989). Kirchman & Botta (2007) have argued that yeast aging assays testing the importance of mitochondrial function should be performed on a glycerol medium because this pushes metabolic pathways generating energy into a mode more similar to that of mammalian cells. Under these conditions, copper supplementation is associated with life span extension, possibly through the upregulation of oxygen-radical defense mechanisms.…”
Section: Yeast and Neurodegenerationmentioning
confidence: 99%
“…Yeast, being facultative anaerobes, generate energy primarily from fermentation when glucose is available and switch to a primarily respiratory growth state either when glucose is depleted or when they are grown on a non-fermentable carbon source such as glycerol (Gancedo & Serrano 1989). Kirchman & Botta (2007) have argued that yeast aging assays testing the importance of mitochondrial function should be performed on a glycerol medium because this pushes metabolic pathways generating energy into a mode more similar to that of mammalian cells. Under these conditions, copper supplementation is associated with life span extension, possibly through the upregulation of oxygen-radical defense mechanisms.…”
Section: Yeast and Neurodegenerationmentioning
confidence: 99%
“…To examine the possibility that the increased iron reduces oxidative stress to extend life span we analyzed the effect of iron supplementation on the life spans of SOD1 (Cu/Zn SOD) and SOD2 (MnSOD) mutants. Previous research has shown that copper supplementation partially restores life span in these mutants (Kirchman & Botta, 2007). If copper’s effect was in fact due to increased iron uptake by the cells, then iron supplementation should have similar results.…”
Section: Resultsmentioning
confidence: 91%
“…We previously determined that copper’s influence on yeast longevity was not through the copper containing enzyme Cu/Zn SOD (Kirchman & Botta, 2007). This lead us to hypothesize that copper was acting indirectly to influence longevity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations